Overcoming the Uncanny Valley Theory in Digital Characters Based on Human Attitudes - Laja Uggah, Louis; Abdul Manaf, Ahmad Azaini (Universiti Putra Malaysia Press+, 2015)
The uncanny valley theory is an idea pioneered by Masahiro Mori in 1970 in relation to the psychological effects of lifelike robotics (Mori, 1970). The uncanny valley is a phenomenon that occurs in animation and robotic, wherein things that look extremely similar to the human face, but with slight differences from the natural appearance or the natural movements and expressions of humans, that are found to be disturbing, uncanny, and revolting (Mewes & Heloir, 2009). This study aimed to accomplish three goals: 1) analysing the participants’ attitudes towards digital characters based on a series of validated semantic differential questionnaires; 2) developing a conceptual model focusing on overcoming the uncanny valley theory in computer generated digital characters based on empirical findings; and 3) validating the theoretical model by providing specific guidelines for overcoming the uncanny valley theory by avoiding negative human attitude responses. Based on results from 229 participants, this study examined the key factors of digital characters from games and movies which caused uncanny responses from the participants based on their attitudes. The structural model indicates that digital characters’ facial expressions have the strongest influence on the participants’ perceived humanness, followed by the stimulus’s physical movements. Meanwhile, the digital characters’ animated hair has the next strongest influence on the participants’ familiarity, followed by its facial expression.